Determinants of household water and energy access and their impacts on food security and health outcomes in Sudan - Kirui, Oliver K.; Ahmed, Mosab O. M.; Raouf, Mariam; Abushama, Hala; Siddig, Khalid (International Food Policy Research Institute, 2024)
This study investigates the determinants of access to safe water and reliable energy for households in Sudan using nationally representative data from a recent labor market survey. The results show that urbanization, education, and wealth significantly enhance the access households have to these essential services, while rural areas and less developed regions, particularly in the Darfur and Kordofan regions, face substantial challenges. Access to reliable energy correlates with better food security and health outcomes within households, and improved access to safe water significantly enhances the health of household members. Policy recommendations supported by these research results include targeted rural infrastructure investments, educational improvements, and regional interventions to address disparities in household access to safe water and reliable energy across Sudan.